"A Toste wett in Muskadine": Preventing Miscarriage in Early Modern English Recipe Books c.1600–1780. Issue 4 (2nd October 2022) - Evans, Jennifer
ABSTRACT: Discussions about early modern miscarriage have considered in detail how women rationalised miscarriage framing the emotional burden of loss within the context of providence and sin. This valuable interpretation considers women from the moment at which the miscarriage had occurred. The experience of miscarriage, though, did not start at the moment of loss, it began with the first concerns that a foetus was at risk. By the time women were considering their sins women had already read the signs of their bodies and, perhaps, consumed remedies to prevent the miscarriage from occurring. This article investigates remedies designed to prevent miscarriage that were shared in manuscript recipe collections. These reveal a female-centred community of knowledge that favoured recipes attested by women's experiences. The medicines circulating in early modern recipe collections emphasise the central position of women's sensations and emotions to antenatal care.